ANALISIS INFORMED CONSENT TERHADAP PERLINDUNGAN HUKUM TENAGA KESEHATAN DI RUMAH SAKIT UMUM DAERAH KOTA BANDUNG - Wahyudi, Dhita Annisa (Fakultas Hukum Universitas Komputer Indonesia, 2020)
The research aims to determine the analiysis of informed consent to the health staff legal protection at bandung regional public hospital. Informed consent is an agreement of medical action through a process of communication between the doctor and the patient about the agreement of medical action that the medical staff would do to the patient. The research method used is a juridical normative qualitative research method with a descriptive approach. Data collection techniques used are by way of literature studies related to the subject, interviews and field observations. The results of the research showed that in general the informed consent at bandung regional public hospital had been optimally implemented and in accordance with the SOP (Standard Operating Procedure) in the hospital and there was also a General Consent, it’s a general agreement of the patient. Informed consent that has been optimally implemented and in accordance with the regulations in this hospital could protect the health staff and medical staff in carrying out medical actions on patients. For the suggestion given by researchers about health staff and medical staff have to give the socialization about the procedures of informed consent and medical staff have to understand about statute of law that exist, especially to the health staff and the hospital regulations